Experimental Investigation of the Flow on a Simple Frigate Shape (SFS) - Rafael Bardera Mora (The Scientific World Journal)
Helicopters operations on board ships require special procedures introducing additional limitations known as ship helicopter operational limitations (SHOLs) which are a priority for all navies. This paper presents the main results obtained from the experimental investigation of a simple frigate shape (SFS) which is a typical case of study in experimental and computational aerodynamics. The results obtained in this investigation are used to make an assessment of the flow predicted by the SFS geometry in comparison with experimental data obtained testing a ship model (reduced scale) in the wind tunnel and on board (full scale) measurements performed on a real frigate type ship geometry.